Review of the Australian endemic genus Tasmosalpingus Lea, 1919 (Coleoptera, Cucujoidea, Tasmosalpingidae) - Liu, Zhenhua; Porch, Nicholas; Ślipiński, Adam (Zootaxa, 2023)
The sole genus of the Australian endemic family Tasmosalpingidae, Tasmosalpingus Lea, 1919, is revised and T. promiscuus Lea, 1919 is proposed as a junior synonym of T. quadrispilotus Lea, 1919. T. magnus sp. nov. is described from New South Wales and Victoria, representing the northernmost distribution of this family. A predicted distribution of the genus is given, and the relationships between Tasmosalpingidae, Cyclaxyridae and Lamingtoniidae are discussed.